Perbedaan Kekuatan Geser dan Kekuatan Tarik pada Restorasi Resin Komposit Microhybrid dengan Bonding Generasi V dan Bonding Generasi VII - Susra, Winda; Listya Nur, Desi; Puspita, Sartika (Insisiva Dental Journal, 2013)
Microhybrid composite resin is current development of a hybrid composite resin which has particle size of 0.6- 0.8 µm in average and 0.04µm as filler for 78% of the whole weight that have contribution to improve mechanical properties. A bonding agent is required to bond composite resin into tooth. It has a function to embed composite resin as restorative material, therefore it has to had a good adhesive strength. This study has purpose to determine the differences between shear and tensile bond strength of V and VII bonding agent generation in the microhybrid composite resin restoration. The study was in vitro experimental laboratory with 20 samples of post-extraction-caries-free premolars. The samples were cut through dentin. Before microhybrid resin composite was applied into the samples, they were equally separated into two groups. Fifth bonding agent generation was applied on first group and seventh bonding agent generation was applied on second group then incubated for 24hours at room temperature. It was tested in the term of shear and tensile bond strength by universal testing machine at speed 0.5mm/second. The result showed significance shear and tensile bond strength between two groups (p<0,05) by Independent Sample T-Test. It can be concluded that V bonding agent generation has greater shear and tensile strength than VII bonding agent generation.